Comprehensive Analysis of the Transcriptome-Wide m6A Methylation in Mouse Pachytene Spermatocytes and Round Spermatids - Hong, Shihao; Shen, Xiaozhong; Cheng, Jinmei; Tang, Hanyu; Sun, Fei (Frontiers in Genetics, 2022)
Spermatogenesis, an efficient and complex system in male germline development, requires a series of elaborately regulated genetic events in which diploid spermatogonia differentiate into haploid spermatozoa. N6-methyladenosine (m6A) is an important epigenetic RNA modification that occurs during spermatogenesis. ALKBH5 is an m6A eraser and knocking out Alkbh5 increases the level of total m6A methylation and causes male infertility. In this study, comprehensive analyses of MeRIP-seq and RNA-seq data revealed differences between wild-type (WT) and Alkbh5 knockout (KO) mice. In pachytene spermatocytes (PA), 8,151 m6A peaks associated with 9,959 genes were tested from WT and 10,856 m6A peaks associated with 10,016 genes were tested from KO mice. In the round spermatids (RO), 10,271 m6A peaks associated with 10,109 genes were tested from WT mice and 9,559 m6A peaks associated with 10,138 genes were tested from KO mice. The peaks were mainly concentrated in the coding region and the stop codon of the GGAC motif. In addition, enrichment analysis showed significant m6A methylation genes in related pathways in spermatogenesis. Furthermore, we conducted joint analyses of the m6A methylome and RNA transcription, suggesting an m6A regulatory mechanism of gene expression. Finally, seven differentially expressed mRNAs from RNA-seq data in both PA and RO were verified using qPCR. Overall, our study provides new information on m6A modification changes between WT and KO in PA and RO, and may provide new insights into the molecular mechanisms of m6A modification in germ cell development and spermatogenesis.